2018
DOI: 10.2188/jea.je20170012
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Levels of Sedentary Behavior and Physical Activity in a General Japanese Population: The Hisayama Study

Abstract: BackgroundThe purpose of this cross-sectional study was to describe the patterns and levels of sedentary time and physical activity (PA) in a general Japanese population.MethodsA total of 1,740 community-dwelling Japanese adults aged ≥40 years participated in this study. Sedentary time and PA were assessed for 7 consecutive days using a tri-axial accelerometer. Daily patterns and levels of sedentary time and PA were calculated by sex, age group (40–64, 65–74, and ≥75 years), and body mass index (BMI; <25 and ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…Of these, eight reported age to be positively associated with SB while seven found no significant relationship. Despite these seemingly mixed findings, age was positively associated with total SB in the three studies that assessed SB with an accelerometer . Sex as an SB correlate was assessed in 22 studies with most reporting no significant association.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Of these, eight reported age to be positively associated with SB while seven found no significant relationship. Despite these seemingly mixed findings, age was positively associated with total SB in the three studies that assessed SB with an accelerometer . Sex as an SB correlate was assessed in 22 studies with most reporting no significant association.…”
Section: Resultsmentioning
confidence: 87%
“…In terms of PA correlates, results were not consistent. An accelerometer study from China found that higher volume of MVPA was associated with less total SB . In contrast, an Omani research team observed more self‐reported MVPA to be associated with more total SB .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations